Degradation of cylindrospermopsin by using polymorphic titanium dioxide under UV-Vis irradiation - Zhang, G.; Nadagouda, M.N.; O'Shea, K.; El-Sheikh, S.M.; Ismail, A.A.; V. Likodimos; P. Falaras; Dionysiou, D.D. (Catalysis Today, 2014)
The frequent occurrence of cyanobacterial harmful blooms due to eutrophication necessitates the development of appropriate water treatment technologies for the released cyanotoxins. In this study, nanoparticles composed of anatase-brookite-rutile polymorphic titanium dioxide (PM-TiO2) were synthesized using a modified sol-gel method with a low temperature oil bath for the photocatalytic degradation of cylindrospermopsin (CYN), an important cyanotoxin that has been only little explored with respect to water treatment technologies. The physiochemical properties of synthesized PM-TiO2 nanoparticles, such as the formation of heteronanostructure (with 66% anatase, 22% brookite and 12% rutile), high surface area (207 m2/g), small particle size (∼5 nm), and bandgap (Eg = 3.0 eV), endow PM-TiO2 to be an effective photocatalyst for CYN treatment under UV-Vis irradiation. Moreover, the impacts of certain process parameters (i.e. photocatalyst loading, pH and presence of natural organic matter (NOM)) were examined and discussed in detail. It was found that the presence of NOM decreased the observed reaction rate constants by 52% and 95% compared to clean water samples when 2 and 10 mg/L NOM were applied, respectively. In particularly, when two natural water samples from East Fork Lake and Toledo Water Plant were applied as the matrices in the photocatalytic experiments, the degradation rate constants were reduced by 90% and 75%, respectively. This work demonstrates that the polymorphic TiO2 containing three phases can be effective photocatalyst for cyanotoxin treatment, however, the degradation kinetics are inhibited significantly in the presence of NOM. Therefore, pretreatment is necessary to remove NOM before the photocatalytic treatment of surface water containing CYN. © 2013 Elsevier B.V.